KAJIAN POTENSI AIR PERMUKAAN SEBAGAI BAHAN BAKU WATER TREATMENT PLANT DI KAWASAN MARINA CITY BATAM - Bahri, Ahmad Muda; Raza'i, Tengku Said; Viruly, Lily; Ismail, Khodijah (Universitas Pakuan, 2025)
The rapid population growth of Batam City has a significant impact on the availability of clean water, especially around Marina City Sekupang Tanjung Riau. In response to this, BP Batam and the developer of Marina City Sekupang plan to optimize the local natural reservoir as a source of raw water for the WTP (Water Treatment Plant). This study aims to evaluate the potential discharge and water quality in the natural lake in the Marina City area, Batam. The methodology uses a quantitative approach for hydrological analysis, including calculating flood discharge and determining the area of the water catchment area, based on direct field measurements. Social analysis uses a qualitative descriptive method. Water sampling follows the SNI 6989.57: 2008 procedure. The results of the study show that the estimated domestic water requirement per house connection in 2023 reaches 50.47 liters/second. Annual water evaporation is calculated based on the average evaporation rate in the Marina City lake of 22.29 mm/month or 0.776 mm/day. The total reservoir capacity is 869,249.00 m3, with a total water loss of 262,851 m3/day. This research provides important information for the development of water resources in the Marina City area, supporting efforts to meet the clean water needs of the local community and its surroundings